Edmonton Obesity Staging System: an improvement by cardiopulmonary exercise testing - Bettini, Silvia; Quinto, Giulia; Neunhaeuserer, Daniel; Battista, Francesca; Belligoli, Anna; Milan, Gabriella; Gasperetti, Andrea; Vettor, Roberto; Ermolao, Andrea; Busetto, Luca (International Journal of Obesity, 2021)
Different approaches are used to classify obesity severity. Beyond classical anthropometric measurements, the Edmonton Obesity Staging System (EOSS) considers medical, physical and psychological parameters. However, this method has some limitations, principally due to the absence of an objective measure for physical impairment. The aim of our study is thus to overcome this limitation suggesting a new functional parameter obtained by cardiopulmonary exercise testing (CPET), i.e., cardiorespiratory fitness (CRF), expressed as weight-adjusted peak oxygen consumption (VO peak/kg). This observational cross-sectional study conducted on a population of 843 patients affected by obesity finally enrolled 500 subjects. Every patient underwent clinical, anthropometric, biochemical assessment and CPET. First, participants have been classified according to standard EOSS in five stages. Second, patients were reclassified according to the new modified EOSS (EOSS-CRF) based on their age- and gender-appropriate VO peak/kg percentiles as reported in the healthy normal-weight population of the FRIEND registry. VO peak/kg was significantly different between standard EOSS classes 1 and 2 and classes 1 and 3 (ANCOVA p model = 0.004), whereas patients in classes 2 and 3 showed similar CRF. The EOSS-CRF classification varied in number of patients in each class compared to EOSS, particularly with a shift from class 2 to class 3. Moreover, CRF showed that physical impairment is less addressed by EOSS when compared to EOSS-CRF. The integration of EOSS with CRF allowed us to assign to each patient a severity index that considers not only clinical parameters, but also their functional impairment through a quantitative and prognostically important parameter (VO peak/kg). This improvement of the staging system may also provide a better approach to identify individuals at increased risk of mortality leading to targeted therapeutic management and prognostic risk stratification for patients with obesity.